Mindfulness: An effective technique for various psychological problems - Pratikta, Arihdya Caesar (Universitas Negeri Yogyakarta, 2020)
Mindfulness recently has gained its popularity amongst therapeutic researchers and practitioners. As a part of therapy sessions, mindfulness highlights the urgency of the relationship between therapists and clients as this factor can strongly predict the therapeutic outcomes. This article will discuss issue and several mindfulness-related aspects. The remainder will be organised into six sections, including: the definition of mindfulness, the importance of relationship in mindfulness, measurement the outcomes of mindfulnes, several mindfulness-based therapies, the benefits of mindfulness from various empirical studies, summarising the presented explanations and offering suggestions for future research. Researchers and practitioners have developed various mindfulness-based therapies. It also imply the practice of counseling. Counseling with mindfulness-based can effectively help people who suffer from various psychological problems, ranging from anxiety disorders to trauma and posttraumatic stress disorder. Nevertheless, it warrants further research to overcome the current research flaws, such as the number of sample size, methodological procedures, and replicated findings.